Principal Leadership Effectiveness and Some the Determinant Variable - Basyaruddin Daulay; Zainuddin; Nasrun (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to answer eight problems related to leadership effectiveness. It is realized that the quality of education in general and the achievement of students in particular is not a stand-alone thing, but it is the result of a learning process that is determined by various factors such as principals, teachers, students, curriculum, source books, libraries, laboratories, and facilities. other supports. The population of this study was the principal of a high school in Medan, amounting to 231 people. Sampling was carried out using a stratified proportional random sampling technique using the Cochran formula to produce a sample of 114 people. The research instrument used a questionnaire with a Likert. Research data is processed and analyzed by path analysis. The results of this study indicate that there is a direct effect of job design on managerial competence 0.5881; job design on achievement motivation 0.3105; job design on leadership effectiveness 0.2481; interpersonal communication on managerial competence 0.1428; interpersonal communication on achievement motivation 0.2573; interpersonal communication on leadership effectiveness 0.1779; teacher managerial competence on leadership effectiveness 0.1644; and achievement motivation on leadership effectiveness 0.1893. It can be stated that increasing the effectiveness of the principal's leadership can be done through job design, interpersonal communication, managerial competence, and achievement motivation.